Microtia and short stature: a new syndrome. Issue 11 (November 1991) - Cohen, B; Temple, I K; Symons, J C; Hall, C M; Shaw, D G; Bhamra, M; Jackson, A M; Pembrey, M E
Abstract : Bilateral microtia, absent patellae, short stature, poor weight gain, and characteristic facial features are described in two female sibs. Other skeletal anomalies included complete habitual dislocation of the elbow, slender ribs and long bones, abnormal modelling of the glenoid fossae with hooked clavicles, and clinodactyly. Bone age was significantly delayed and there was flattening of the epiphyses. This unusual combination of features has many similarities to the syndrome described by Hurst et al.